PENINGKATAN ASPEK MOTORIK KASAR MELALUI KONTEN VIRAL (FYP) APLIKASI TIK TOK UNTUK ANAK USIA 5-6 TAHUN DI TK PERTIWI 42 GAYAMSARI - Santoso, Didik Ardi; Purwandasari, Annisa Sa’adah; Sukiram, M.; Ratno, Ratno (Dharmas Education Journal (DE_Journal), 2022)
This research aims to improve gross motor skills through viral content (FYP) on the TikTok application for children aged 5-6 years at TK Pertiwi 42 Gayamsari. The research method used in this study is classroom action research (CAR) with a procedure of 2 cycles, each consisting of 2 meetings. The data collection techniques employed by the researcher include observation and documentation with the subjects being Group B, consisting of 23 children. The results of this classroom action research indicate that the use of viral content (FYP) from the Tik Tok application can improve the gross motor skills of children aged 5-6 years, with initial conditions reaching 43% with the description of Starting to Develop (MB) in the pre-cycle, reaching 62% in Cycle I with the description of Developing as Expected (BSH), and increasing to 84% in Cycle II with the description of Developing Very Well (BSB). Therefore, through this research, the utilization of viral content (FYP) from the Tik Tok application can enhance the gross motor skills of children aged 5-6 years at TK Pertiwi 42 Gayamsari because it can attract children's attention and enthusiasm in movement activities.